The development of comic media based on Sekujang culture for elementary school students - Atika Susanti; Abdul Muktadir; Ady Darmansyah (Journal of Research in Instructional, 2025)
Elementary students' cognitive learning outcomes remain a challenge, particularly in understanding, remembering, and applying taught concepts. Low cognitive achievement is often caused by a lack of student engagement, unappealing teaching methods, and minimal use of interactive and contextual learning media. This study aims to develop and assess the feasibility of Sekujang culture-based comic media and determine its effectiveness in enhancing students' cognitive learning outcomes in Bahasa Indonesia learning. Using the R&D method with the ADDIE model, this study found that the comic media met the "very feasible" criteria based on expert assessments. The material validation scores increased from 37 and 39 in stage 1 to 55 and 58 in stage 2, while the design validation scores improved from 35 to 53 and 55. The effectiveness test using a paired t-test yielded a significance value of 0.000, indicating a significant improvement in students' cognitive learning outcomes. The experimental class achieved a gain score of 0.3756 (moderate), while the control class only reached 0.1686 (low). These findings suggest that the Sekujang culture-based comic media is an effective and engaging learning tool for Bahasa Indonesia instruction in elementary schools.